How do learning environments vary by school sector and socioeconomic composition? Evidence from Australian students. (November 2016) - Perry, Laura B; Lubienski, Christopher; Ladwig, James
We examine how students' perspectives of their learning environments vary between private and public schools in Australia. Previous research has shown that educational outcomes do not vary by school sector in most countries after controlling for student social background. Little is known, however, about the ways in which different students' educational experiences vary across sectors. Australia is a good case study for examining this question, because it has one of the largest private school sectors in the world. We used a large and nationally representative dataset to compare sector differences across five measures of learning environments while accounting for the average socioeconomic composition of the school. Very few differences large enough to be considered educationally substantive were found between sectors. On two measures, however, student perspectives varied substantially within sectors and across school socioeconomic contexts. Overall, classroom disciplinary climate varied the most across school sectors and socioeconomic contexts, and teacher scaffolding and structuring strategies varied the least.